Development and validation of a chiral LC-MS/MS method for the separation and quantification of four synthetic cathinones in human whole blood and its application in stability analysis - Aldubayyan, Abdulaziz A.; Castrignanò, Erika; Elliott, Simon; Abbate, Vincenzo (Talanta (Oxford), 2023)
Synthetic cathinones, a subclass of new psychoactive substances, have gained high popularity on the recreational drugs market over the past years. These drugs typically have a chiral center, so they may exist as two stereoisomers. Therefore the pharmacological, pharmacokinetic or metabolic properties of their enantiomers are expected to differ. However, these drugs are often synthesized and sold as a racemic mixture, and as a consequence, differentiation of their (R)- and (S)- enantiomers is relevant in clinical and forensic toxicology. Information about single enantiomers of synthetic cathinones is relatively scarce due to challenges of their chiral analysis. Hence, a sensitive and reliable liquid chromatography-tandem mass spectrometry method was developed and validated for the chiral separation and quantification of four synthetic cathinones in human whole blood samples. The method was fully validated in terms of linearity, limit of detection, limit of quantification, bias, precision, carryover, interferences, matrix effects, recovery and processed sample stability and successfully applied to evaluate the stability as well as enantioselective degradation of synthetic cathinones enantiomers under various storage conditions. For most of the analytes, significant enantioselective degradation was observed when stored at room temperature or refrigerated, with the E2-enantiomers observed to more rapidly degrade under both conditions. This is the first report concerning the stability and enantioselective degradation of synthetic cathinone enantiomers in whole blood. Moreover, the inversion study demonstrated enantiomeric inversion of R-(−)- and S-(+)-methylenedioxypyrovalerone (MDPV) in human whole blood and methanolic solution. [Display omitted] •A chiral LC-MS/MS method for selected synthetic cathinones was developed and validated.•The method was successfully employed to study stability of synthetic cathinone enantiomers in whole blood.•First report on enantiomeric inversion of MDPV.•This method would be useful for future pharmacokinetic studies.